2013
DOI: 10.12955/cbup.v1.19
|View full text |Cite
|
Sign up to set email alerts
|

Technological Entrepreneurship of Small and Medium Business in the Republic of Bulgaria as a Factor for Sustainable Development

Abstract: In the context of deepening economic and social crisis the importance of small and medium enterprises in the Republic of Bulgaria is steadily increasing. They have provided significant number of jobs on the labour market and have created much of the gross domestic product of Bulgaria. Our thesis is that technological entrepreneurship is a factor for the sustainable development of small and medium business in the country as a whole and stimulates overcoming the crisis in the country. This research paper reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Other studies also suggested a rethinking of the current approach for municipal solid waste management in developing countries with a view for municipalities to gradually improve the awareness levels of the community for the adoption of decentralized system in which entrepreneurs will have a key responsibility in solid waste management (Challcharoenwattana and Pharino, 2016;Kirama andMayo, 2016, Ofobruku andEzeah, 2019). It has also been argued that most investigations in solid waste management did not cover the key elements required for the involvement of private entrepreneurs, which has to do with entrepreneurial innovation, from solid waste management and how entrepreneurial capacities could best be applied to optimize efficiencies in solid waste recycling (Ahmed and McQuaid, 2005;Levi Jaksić et al, 2015;Mirchev and Dicheva, 2013;Mitra, 2012). Thus, Research hypothesis: H 0 : There is a significant effect of entrepreneurial innovation on solid waste recycling in Abuja.…”
Section: Entrepreneurial Innovation On Sustainable Solid Waste Recyclmentioning
confidence: 99%
“…Other studies also suggested a rethinking of the current approach for municipal solid waste management in developing countries with a view for municipalities to gradually improve the awareness levels of the community for the adoption of decentralized system in which entrepreneurs will have a key responsibility in solid waste management (Challcharoenwattana and Pharino, 2016;Kirama andMayo, 2016, Ofobruku andEzeah, 2019). It has also been argued that most investigations in solid waste management did not cover the key elements required for the involvement of private entrepreneurs, which has to do with entrepreneurial innovation, from solid waste management and how entrepreneurial capacities could best be applied to optimize efficiencies in solid waste recycling (Ahmed and McQuaid, 2005;Levi Jaksić et al, 2015;Mirchev and Dicheva, 2013;Mitra, 2012). Thus, Research hypothesis: H 0 : There is a significant effect of entrepreneurial innovation on solid waste recycling in Abuja.…”
Section: Entrepreneurial Innovation On Sustainable Solid Waste Recyclmentioning
confidence: 99%